A Study On The Policies That Matter To The Malaysian Unit Trust Industry's Growth And Prospect - Abdullah, Salim (2006)
This thesis paper explores on eof the most popular investment vehicles in financial landscape called unit trust fund or mutual fund. The study will focus on the EPF Member's Investment Scheme, a provision that empowres its member to withdraw their savings for external fund managers, mostly in the form of unit trust.